Holly, reindeer, and colored lights : the story of the Christmas symbols - Barth, Edna.; Arndt, Ursula (New York : Clarion Books, 2000)
Examines the origins of Christmas symbols--trees, ornaments, Yule logs, Santa Claus, cards, Christmas colors, and many other holiday observances.
Originally published: New York : Seabury Press, c1971.
Includes bibliographical references (p. 95) and index.
Elem. School Library Collection
5.0
3-6
Keywords: Christmas -- Juvenile literature; Signs and symbols -- Juvenile literature; Christmas; Signs and symbols; Christmas; Signs and symbols